AH jump duration is associated with elimination of slow pathway during ablation of atrioventricular nodal reentrant tachycardia - Raharjo, Sunu B. (Indian Pacing Electrophysiol J, 2020)
INTRODUCTION: Ablating the slow pathway (SP) is the superior treatment for atrioventricular nodal reentrant tachycardia (AVNRT) with a low complication rate. However, the ablation of the SP could result in either complete elimination or modification of the SP. We aimed to investigate whether the duration of AH jump pre-ablation associated with the outcome of elimination of SP. METHODS: We included 56 patients with typical AVNRT (slow-fast), 20 males and 36 females, aged 44.2 ± 15.1 years. Slow pathway ablation was performed using classical approach. Univariate and multivariate analysis was performed for potential predictors of SP elimination. RESULTS: Typical AVNRT was inducible in all patients. Post-ablation, non-inducibility of AVNRT was obtained in all 56 (100%) patients, with SP elimination in 33 (61%) patients and SP modification in 23 (39%) patients. Patients with SP elimination had significantly longer AH jump than patients with SP modification. Cox regression analysis showed that AH jump duration was the independent predictor of SP elimination, in which every 20 ms increase in AH jump duration was associated with 1.30 higher rate of SP elimination. Furthermore, ROC curve analysis indicated that the AH jump duration of ≥100 ms had 6.14 times higher probability for complete elimination of the SP with a sensitivity of 79%, specificity of 70%, PPV of 79% and NPV of 70%. CONCLUSIONS: AH jump duration pre-ablation is associated with complete elimination of slow pathway during AVNRT ablation.